Targeting of Swi/Snf to the yeast GAL1 UAS(G) requires the Mediator, TAF(II)s, and RNA polymerase II - Lemieux, Karine (Nature Publishing Group, 2004)
The chromatin remodeling activity of the Swi/Snf complex is essential for the expression of several yeast genes. Previous studies have suggested that recruitment of Swi/Snf requires the action of transcriptional activators. However, reports in metazoans and in yeast have provided evidence of interactions between Swi/Snf and the RNA polymerase II holoenzyme/Mediator complex. Here we show that recruitment of Swi/Snf to the galactose-inducible gene GAL1 cannot be fully achieved without the integrity of the Mediator complex, TAF(II)s, and RNA polymerase II. Moreover, artificial recruitment of Mediator is sufficient to tether both Swi/Snf and SAGA to the GAL1 UAS(G). We further demonstrate that Swi/Snf recruitment at GAL1 does not require acetylation of chromatin by Gcn5 nor the presence of SAGA. Based on these results, we conclude that interactions between the Gal4 activator and Swi/Snf are not sufficient to recruit the latter to the GAL1 UAS(G), since interactions with the Mediator, TAF(II)s, and RNA polymerase II are also important.